Comparative proteomic analysis identifies proteins associated with arbuscular mycorrhizal symbiosis in Poncirus trifoliata - Yu, Huimin; Ji, Chuanya; Zheng, Zijun; Yu, Miao; Liu, Yongzhong; Xiao, Shunyuan; Pan, Zhiyong (Frontiers in Plant Science, 2023)
Citrus, one of the most widely cultivated fruit crops in the world, relies on arbuscular mycorrhizal fungi (AMF) to absorb nutrients and water from soil. However, the molecular mechanism of AM symbiosis (AMS) in citrus in general have largely been understudied. Here, using a TMT labeling proteomic approach, we identified 365 differentially expressed proteins (DEPs) in roots of Poncirus trifoliata (a common citrus rootstock) upon Rhizophagus irregularis colonization as compared with uninoculated roots, of which 287 were up-regulated and 78 were down-regulated. GO analysis revealed that the DEPs were mainly involved in biological processes such as negative regulation of endopeptidase inhibitor activity, negative regulation of endopeptidase, one-carbon metabolic process and carbohydrate metabolic process. KEGG enrichment analysis indicated that the DEPs were mainly involved in regulating metabolic pathways such as fatty acid biosynthesis, phenylpropanoid biosynthesis and carbon metabolism. Furthermore, 194 of the 365 DEPs were found to be associated with AMS-responsive genes by association analysis with our previous transcriptomes data, which highlighted the important roles of these proteins in AMS. One of the 194 DEPs, neutral ceramidase (PtNCER), was further chosen for function analysis via RNAi interfering its homologous gene MtNCER in a mycorrhizal model plant Medicago truncatula, which confirmed a positive role of NCER in AM establishment. Our results provided basic data and key candidate genes for genetic improvement of efficient nutrient uptake through AM establishment in citrus and other crops.